1.3t+4.6=2.5t-0.3-1.4t

Simple and best practice solution for 1.3t+4.6=2.5t-0.3-1.4t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.3t+4.6=2.5t-0.3-1.4t equation:


Simplifying
1.3t + 4.6 = 2.5t + -0.3 + -1.4t

Reorder the terms:
4.6 + 1.3t = 2.5t + -0.3 + -1.4t

Reorder the terms:
4.6 + 1.3t = -0.3 + 2.5t + -1.4t

Combine like terms: 2.5t + -1.4t = 1.1t
4.6 + 1.3t = -0.3 + 1.1t

Solving
4.6 + 1.3t = -0.3 + 1.1t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1.1t' to each side of the equation.
4.6 + 1.3t + -1.1t = -0.3 + 1.1t + -1.1t

Combine like terms: 1.3t + -1.1t = 0.2t
4.6 + 0.2t = -0.3 + 1.1t + -1.1t

Combine like terms: 1.1t + -1.1t = 0.0
4.6 + 0.2t = -0.3 + 0.0
4.6 + 0.2t = -0.3

Add '-4.6' to each side of the equation.
4.6 + -4.6 + 0.2t = -0.3 + -4.6

Combine like terms: 4.6 + -4.6 = 0.0
0.0 + 0.2t = -0.3 + -4.6
0.2t = -0.3 + -4.6

Combine like terms: -0.3 + -4.6 = -4.9
0.2t = -4.9

Divide each side by '0.2'.
t = -24.5

Simplifying
t = -24.5

 

See similar equations:

| -9-7y=5 | | 7(t+3)=35 | | 100y=5x+40 | | 5(x+3)-4=3x+2(4+x) | | -3x-4=2x+6 | | 6x-4=2x-32 | | x^3-2x^2+9x+18=0 | | 5-6w=41 | | 3.5+2.5y=2y-4 | | -7x+7=14 | | y=.05x+.4 | | 5=x+9 | | -3=13-3x | | .5x=6 | | 8(5y+7z)-56z= | | -4y+4=-4(2y+4) | | 171x-32=3x | | 50=2x+5y | | 5x+y=-27 | | 3n+5n=144 | | x^2+7x-40=0 | | 9(19x-4)=3x | | 2x(3+2x)=0 | | 9b^2-30b+25=0 | | -[6x+(4x+5)]=7-(3x+7) | | 5X^2-6X-1=0 | | x-.45=5.97 | | 24(x-1)=2(12+4)-32 | | y-6.32=.73 | | 24(x-1)=2(12x+4)-32 | | 3(y+5)= | | -6(4-k)= | | 9x^2+12x=0 | | X-8=-26 | | 3(2x-4)=48 | | -100=-4z | | 4r=44 | | -10k=170 | | 5x^2-16x+3=0 | | 8n=-32 | | 3x+17=41 | | 3y+10=2y+20 | | x^2+2xy+y^2=0 | | 30=-y | | -2x-10=4 | | 7(9+x)+9(13-x)=154 | | 8x+100=300 | | 7p+15-1510p=6 | | -54=-6q | | -6(3t+3)=18 | | 7x+18=3x+46 | | 19n-9n+n-11=22 | | -54=9q | | 9+4+4=25 | | 9+4x+4=25 | | 4x+5yi=32-25i | | -16v=-32 | | 5x=-75 | | 39=-3w | | -x=-24 | | 5-0.67(2k-1)=7 | | 72=6m | | 2x^2+16x-40=0 | | -y=-2x+30 | | -3x+73=-(-2x)+32 |